The aqueous extract of rhizome of Gastrodia elata Blume attenuates locomotor defect and inflammation after traumatic brain injury in rats. (5th June 2016) - Ng, Chun-Fai; Ko, Chun-Hay; Koon, Chi-Man; Chin, Wai-Ching; Kwong, Hiu Ching Sonya Themis; Lo, Anthony Wing-Ip; Wong, Hing-Lok; Fung, Kwok-Pui; Lau, Clara Bik-San; Lam, Ping-Kuen; Poon, Wai Sang; Leung, Ping-Chung
Abstract: Ethnopharmacological relevance: Traumatic brain injury (TBI) has an incident rate of 200–300 people per 100, 000 annually in the developed countries. TBI has relatively high incidence at an early age and may cause long-term physical disability. Patients suffered from severe TBI would have motor and neuropsychological malfunctions, affecting their daily activities. Traditionally, Gastrodia elata Blume is a Chinese Medicines which was used for the head diseases, while their efficiency on reducing brain damage was still largely unknown. In the present study, we aimed to examine the effect of water extract of G. elata Blume (GE) against TBI and elucidate its underlying mechanism. Materials and methods: Sprague-Dawley rats were treated with GE for 7 days, immediately after controlled cortical impact-induced TBI. Impaired neurobehavioral functioning was measured on day 3 and 6 after TBI. Histology of TBI was examined to assess the extent of inflammation, and the expressions of pro-inflammatory cytokines were examined by immunofluorescence study on day 7. Results: GE treatment significantly improved the impaired locomotor functions induced by TBI. GE treatment reduced inflammation and gliosis in the penumbral area. The increase in brain levels of pro-inflammatory cytokines interleukin-6 and tumor necrosis factor-alpha observed in non-GE treated TBI rats were also reversed. Conclusions: GE treatment attenuated the locomotor deficit caused by TBI. The anti-inflammatory activity might be mediated by inhibition of pro-inflammatory cytokines responses in the TBI-brain. Graphical abstract: